An overview of assessment and management of acute dental pain. Issue 3 (September 2022) - Jadun, Sarah; Shah, Aneesha
Dental care practitioners are often the first port of call for patients presenting with acute dental pain. Due to the increasing backlog of patients in the UK resulting from the COVID-19 pandemic, it is expected that an increasing number of patients will present to dental care practitioners with acute dental problems. This article aims to provide an overview of common presentations of acute dental pain, the importance of thorough assessment and accurate diagnosis, and the management of such conditions.